Biblical studies on the Internet a resource guide - Worth, Roland H., 1943-; ebrary, Inc. (Jefferson, N.C. : McFarland, 2008)
"The new edition includes more than 4,800 resources available at more than 10,000 Internet sites that provide information on a range of biblical study topics including Bible translations in English and other languages, audio translations, commentaries, dictionaries, and other resource materials including ones in Greek, Hebrew and other ancient languages"--Provided by publisher.
Includes index.
Electronic reproduction.
Keywords: Bible -- Study and teaching -- Bibliography; Internet; Electronic books